2017
DOI: 10.1002/pbc.26733
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of plexiform neurofibroma in children and adolescents with neurofibromatosis type 1 by [18F]FDG‐PET imaging. Is it of value in asymptomatic patients?

Abstract: Results: A total of 104 examinations were performed. Mean age at first PET was 13.5 years (2.6-22.6). Eight patients had at least one malignant lesion; four of these patients were asymptomatic. Two of four symptomatic patients died, while all patients with asymptomatic malignant lesions are alive. All malignant tumours could be identified by PET imaging in both symptomatic and asymptomatic patients. All lesions judged as benign by [ 18 F]FDG imaging and clinical judgment were either histologically benign if re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 52 publications
(107 reference statements)
1
32
0
1
Order By: Relevance
“…The ADC value has been widely used as a marker in soft tissue imaging, and its usage in MRI could represent cellularity in tissues and signify malignancy (18,20). Consistent with this, a study demonstrated serial whole-body 18 F-FDG-PET/CT as an efficient screening tool for the detection of early-stage MPNST in NF1 patients (21). Additionally, these whole-body imaging tools present doctors with information for surgeries.…”
Section: Discussionmentioning
confidence: 66%
“…The ADC value has been widely used as a marker in soft tissue imaging, and its usage in MRI could represent cellularity in tissues and signify malignancy (18,20). Consistent with this, a study demonstrated serial whole-body 18 F-FDG-PET/CT as an efficient screening tool for the detection of early-stage MPNST in NF1 patients (21). Additionally, these whole-body imaging tools present doctors with information for surgeries.…”
Section: Discussionmentioning
confidence: 66%
“…Azizi et al [ 19 ] recently published a study comprising data on symptomatic and asymptomatic NF1 patients showing the value of FDG PET in the work-up of NF1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…FDG-PET/CT-guided percutaneous biopsy is an effective procedure and the most dependable approach for untimely detection of NF1-associated MPNST (16,17). Benign PNFs demonstrate low fludeoxyglucose (FDG) uptake, whereas MPNSTs depict moderate to high FDG accumulation.…”
Section: Imaging Evaluation Of Pnsts -Differentiation Of Benign and Mmentioning
confidence: 99%